Serious Inadequacies in High Alert Medication-Related Knowledge Among Pakistani Nurses: Findings of a Large, Multicenter, Cross-sectional Survey - Salman, Muhammad; Mustafa, Zia Ul; Rao, Alina Zeeshan; Khan, Qurat-ul-Ain; Asif, Noman; Hussain, Khalid; Shehzadi, Naureen; Khan, Muhammad Farhan Ali; Rashid, Amir (Frontiers in Pharmacology, 2020)
Introduction: Deaths-related to medications errors are common in Pakistan but these are not accurately reported. Recently, the death of a nine months old baby due to abrupt administration of 15% potassium chloride injection sparked the issue of high alert medications (HAMs) related errors in the country. Since drug administration is the prime responsibility of the nurses, it is pivotal that they possess good knowledge of HAMs. Since there is no published data regarding the knowledge of HAMs among Pakistani nurses, we aimed to assess knowledge of HAMs among registered nurses of Pakistan. Methods: A cross-sectional study was conducted among registered nurses, recruited using a convenient sampling technique, from 29 hospitals all over the Punjab Province. Data were collected using a validated self-administered instrument. All data were entered and analyzed using SPSS version 22. Results: The study sample was comprised of 2363 registered nurses (staff nurses = 94.8%, head nurses = 5.2%). Around 63% were working in tertiary hospitals whereas almost 25% and 12% were from district headquarter hospitals and tehsil headquarter hospitals, respectively. Around 84% of the study participants achieved scores < 70%, indicating majority of Pakistani nurses having poor knowledge of HAMs administration as well as regulation. There was no significant difference of overall knowledge among age, hospitals, departments, training, designations, qualification and experience categories. Major obstacles encountered during HAMs administration were ‘getting uncertain answers from colleagues’ (72.9%), ‘unavailability of suitable person to consult’ (61.1%) and ‘receiving verbal orders’ (55.6%). Conclusion: Our study revealed the serious inadequacies in HAMs knowledge among Pakistani nurses which may lead to adverse patient outcomes. Nurses should receive comprehensive pharmacology knowledge not only during in-school nursing education but also as hospital-based continuing education. Moreover, it is of immense importance to bridge the gaps between physicians, clinical pharmacists and nurses through effective communication as this will help reduce medication errors and improve patient care.